Prediction and Correlation of the Solubility of Alkali Chlorides in Different Solvent Mixtures and Temperatures - Alavia-Medina, W (Elsevier B.V., 2018)
Based on the Pitzer model modified by Wu et al. for polymer-salt-aqueous two-phase ternary systems at ambient temperature, this work aims to extend such a model to quaternary systems consisting of a polymer, two salts, and water at different temperatures. This new model is applied to the correlation and prediction of the liquid-solid equilibrium (LSE) of the quaternary systems NaCl+KCl+PEG4000+H2O at 298 K and NaCl+KCl+C2H5OH+H2O at 298 and 313 K. The model contains six binary parameters and ten mixture parameters. The binary parameters are estimated from the liquid-vapor equilibrium (LVE) data of the corresponding salt-water binary systems, while the mixture parameters are obtained from solubility data of ternary systems. The results show that the predicted solubility values of the salt in the quaternary systems are consistent with the experimental data reported in the literature. Better agreement is obtained when the polymer-salt-salt mixture parameter is included. The influence of temperature and the solvent type on the parameters are also discussed in this work. The results provide useful information for the simulation of extractive crystallization processes of inorganic salts with a polymer or an alcohol as the solvent. © 2018 Elsevier B.V.